USMG5 Ashkenazi Jewish founder mutation impairs mitochondrial complex V dimerization and ATP synthesis. (18th June 2018) - Barca, Emanuele; Ganetzky, Rebecca D; Potluri, Prasanth; Juanola-Falgarona, Marti; Gai, Xiaowu; Li, Dong; Jalas, Chaim; Hirsch, Yoel; Emmanuele, Valentina; Tadesse, Saba; Ziosi, Marcello; Akman, Hasan O; et al.
Abstract: Leigh syndrome is a frequent, heterogeneous pediatric presentation of mitochondrial oxidative phosphorylation (OXPHOS) disease, manifesting with psychomotor retardation and necrotizing lesions in brain deep gray matter. OXPHOS occurs at the inner mitochondrial membrane through the integrated activity of five protein complexes, of which complex V (CV) functions in a dimeric form to directly generate adenosine triphosphate (ATP). Mutations in several different structural CV subunits cause Leigh syndrome; however, dimerization defects have not been associated with human disease. We report four Leigh syndrome subjects from three unrelated Ashkenazi Jewish families harboring a homozygous splice-site mutation (c.87 + 1G>C) in a novel CV subunit disease gene, USMG5 . The Ashkenazi population allele frequency is 0.57%. This mutation produces two USMG5 transcripts, wild-type and lacking exon 3. Fibroblasts from two Leigh syndrome probands had reduced wild-type USMG5 mRNA expression and undetectable protein. The mutation did not alter monomeric CV expression, but reduced both CV dimer expression and ATP synthesis rate. Rescue with wild-type USMG5 cDNA in proband fibroblasts restored USMG5 protein, increased CV dimerization and enhanced ATP production rate. These data demonstrate that a recurrent USMG5 splice-site founder mutation in the Ashkenazi Jewish population causes autosomal recessive Leigh syndrome by reduction of CV dimerization and ATP synthesis.